2011
DOI: 10.1017/s000711451100523x
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry anthocyanins: protection against ageing and light-induced damage in retinal pigment epithelial cells

Abstract: Retinal pigment epithelium (RPE) cells are vital for retinal health. However, they are susceptible to injury with ageing and exposure to excessive light, including UV (100-380 nm) and visible (380-760 nm) radiation. To evaluate the protective effect of blueberry anthocyanins on RPE cells, in vitro cell models of replicative senescent and light-induced damage were established in the present study. After purification and fractionation, blueberry anthocyanin extracts (BAE) were yielded with total anthocyanin cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 63 publications
4
76
1
2
Order By: Relevance
“…Taking advantage of consumers' preference for all natural claims could encourage consumers to purchase more blueberries and obtain health benefits from consuming blueberries (Bornsek et al, 2012;Krikorian et al, 2010;Liu et al, 2012;Whyte et al, 2016;Whyte & Williams, 2012). Communicators should work with marketers to identify ways they could use "all natural" or "100% natural" on labels when appropriate to remind shoppers about the nature of blueberries.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of consumers' preference for all natural claims could encourage consumers to purchase more blueberries and obtain health benefits from consuming blueberries (Bornsek et al, 2012;Krikorian et al, 2010;Liu et al, 2012;Whyte et al, 2016;Whyte & Williams, 2012). Communicators should work with marketers to identify ways they could use "all natural" or "100% natural" on labels when appropriate to remind shoppers about the nature of blueberries.…”
Section: Recommendationsmentioning
confidence: 99%
“…Researcher studies have demonstrated that blueberries can improve mobility, protect the heart, improve memory, maintain eye health, and may also act as anti-cancer agents (Bornsek et al, 2012;Liu et al, 2012;Schrager, Hilton, Gould, & Kelly, 2015;Whyte, Schafer, & Williams, 2016;Whyte & Williams, 2012). Consumers' demand for blueberries has been on the rise (U.S. Highbush Blueberry Council, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Supplements containing meso-zeaxanthin are already on the market, but it is unlikely that a study on the scale of the AREDS2 will be conducted to prove its efficacy. Herbal supplements and alternative medicines such as goji berries (153), saffron (154), anthocyanins (155), and flavonoids appear to decrease oxidative stress and are commonly consumed by people concerned about eye diseases such as AMD, but their efficacies and pharmacokinetics are unknown. On the other hand, there is a growing concern among clinicians that excessive intake not only of fat-soluble vitamins and micronutrients, but also minerals and water-soluble vitamins, may be associated with toxicity, including undesirable interactions with other drugs and vitamins.…”
Section: Discussionmentioning
confidence: 99%
“…7 Y. Liu et al investigated the protective effect of blueberry anthocyanin on retinal pigment epithelium through establishing in vitro cell models of replicative senescence and photo-induced injury, and found that blueberry anthocyanin could inhibit the aging of retinal pigment epithelium and protect the cells from photoinduced injury. 8 Anthocyanin can promote the regeneration of rhodopsin and blood circulation, thereby preventing high myopia and improving vision. Gou et al found that at least one of the miR156 targets, SPL9, could directly inhibit anthocyanin biosynthesis and reduce the accumulation of anthocyanin through destabilization of a MYB-bHLH-WD40 transcriptional activation complex.…”
Section: Introductionmentioning
confidence: 99%